Comparative genomics of the Rab protein family in Apicomplexan parasites - Langsley, G.; Noort, V. van; Carret, C.; Meissner, M.; Villiers, Etienne P. de; Bishop, Richard P.; Pain, A. (Elsevier, 2008)
Rab genes encode a subgroup of small GTP-binding proteins within the ras super-family that regulate targeting and fusion of transport vesicles within the secretory and endocytic pathways. These genes are of particular interest in the protozoan phylum Apicomplexa, since a family of Rab GTPases has been described for Plasmodium and most putative secretory pathway proteins in Apicomplexa have conventional predicted signal peptides. Moreover, peptide motifs have now been identified within a large number of secreted Plasmodium proteins that direct their targeting to the red blood cell cytosol, the apicoplast, the food vacuole and Maurer's clefs; in contrast, motifs that direct proteins to secretory organelles (rhoptries, micronemes and microspheres) have yet to be defined. The nature of the vesicle in which these proteins are transported to their destinations remains unknown and morphological structures equivalent to the endoplasmic reticulum and trans-Golgi stacks typical of other eukaryotes cannot be visualised in Apicomplexa. Since Rab GTPases regulate vesicular traffic in all eukaryotes, and this traffic in intracellular parasites could regulate import of nutrient and drugs and export of antigens, host cell modulatory proteins and lactate we compare and contrast here the Rab families of Apicomplexa.